Determination of the two-dimensional distributions of gold nanorods by multiwavelength analytical ultracentrifugation - Simon E. Wawra (Nature Portfolio, 2018)
Characterization of nanoparticles is a complex and important problem for the vast number of applications that require them. Here, the authors present a method to uncover the two-dimensional distribution of length and diameter of anisotropic nanoparticles like gold nanorods with a single measurement by combining spectroscopic and sedimentation data.